Iron angels - Flint, Eric; Kimble, Alistair (Baen, 2017)
"A bizarre kidnapping case leads FBI Special Agent Jasper Wilde into the mysterious world of a strange religious cult and even stranger criminals. At the scene of the kidnapping itself, a frightening apparition is seen. Then a hideously mutilated corpse is found nearby. It doesn't take long before the FBI agents realize something extraordinary is unfolding at the center of Indiana's steel industry. Jasper is joined by Supervisory Special Agent Temple Black who is in charge of the new unit, the Scientific Anomalies Group, which deal with peculiar cases. As the FBI agents race to put a stop to the horrors, they come to understand and accept that something very ancient and very evil has surfaced in the world--or perhaps something very, very alien"--